PRINCIPLES OF THE LEGAL INSTITUTION OF CIVIL REGISTRATION IN THE CONTEXT OF DIGITALIZATION - TROFIMETS Irina Alexandrovna (Правовое государство: теория и практика, 2022)
The purpose of this article is to form the concept of a system of legal principles for the civil registration information system. Methods. In the course of writing the article, various modern methods of scientific cognition are used: logical, historical, legal-technical, formal, comparative, deduction, induction, etc. Results: conclusions are drawn to assess the necessity and expediency of forming the concept of legal principles for the civil registration information system, including general legal and sectoral guidelines for legal regulation of this sphere of public relations. Thus, the construction of a global information society involves the transformation of all spheres of life: economic, social and public administration, in connection with the introduction of technical means and technological processes for collecting, processing, transmitting, exchanging, providing information on civil registration, this public administration sector has transformed into a «Digital Registry Office». The creation of the federal state information system «Unified State Civil Registry» and the Unified Federal Information Register containing information on the population of the Russian Federation, based on data from the information resource of civil registration, has formed a new legal institution in the field of information law, which includes a set of legal norms regulating public relations in the field of civil registration information system, based on specific legal principles.